Deltotrapezial Stabilization of Acromioclavicular Joint Rotational Stability: A Biomechanical Evaluation. Issue 1 (24th January 2023) - Hawthorne, Benjamin C.; Mancini, Michael R.; Wellington, Ian J.; DiCosmo, Michael B.; Shuman, Matthew E.; Trudeau, Maxwell T.; Dorsey, Caitlin G.; Obopilwe, Elifho; Cote, Mark P.; Mazzocca, Augustus D.
Background: Despite advances in surgical management of acromioclavicular (AC) joint reconstruction, many patients fail to maintain sustained anatomic reduction postoperatively. Purpose: To determine the biomechanical support of the deltoid and trapezius on AC joint stability, focusing on the rotational stability provided by the muscles to posterior and anterior clavicular rotation. A novel technique was attempted to repair the deltoid and trapezius anatomically. Study Design: Controlled laboratory study. Methods: Twelve human cadaveric shoulders (mean ± SD age, 60.25 ± 10.25 years) underwent servohydraulic testing. Shoulders were randomly assigned to undergo serial defects to either the deltoid or trapezius surrounding the AC joint capsule, followed by a combined deltotrapezial muscle defect. Deltotrapezial defects were repaired with an all-suture anchor using an anatomic technique. The torque (N·m) required to rotate the clavicle 20° anterior and 20° posterior was recorded for the following conditions: intact (native), deltoid defect, trapezius defect, combined deltotrapezial defect, and repair. Results: When compared with the native condition, the deltoid defect decreased the torque required to rotate the clavicle 20° posteriorly by 7.1% ( P = .206) and 20° anteriorly by 6.1% ( P = .002); the trapezial defect decreased the amount of rotational torque posteriorly by 5.3% ( P = .079) and anteriorly by 4.9% ( P = .032); and the combined deltotrapezial defect decreased the amount of rotational torque posteriorly by 9.9% ( P = .002) and anteriorly by 9.4% ( P < .001). Anatomic deltotrapezial repair increased posterior rotational torque by 5.3% posteriorly as compared with the combined deltotrapezial defect ( P = .001) but failed to increase anterior rotational torque ( P > .999). The rotational torque of the repair was significantly lower than the native joint in the posterior ( P = .017) and anterior ( P < .001) directions. Conclusion: This study demonstrated that the deltoid and trapezius play a role in clavicular rotational stabilization. The proposed anatomic repair improved posterior rotational stability but did not improve anterior rotational stability as compared with the combined deltotrapezial defect; however, neither was restored to native stability. Clinical Relevance: Traumatic or iatrogenic damage to the deltotrapezial fascia and the inability to restore anatomic deltotrapezial attachments to the acromioclavicular joint may contribute to rotational instability. Limiting damage and improving the repair of these muscles should be a consideration during AC reconstruction.